Pain Acceptance and Its Associated Factors among Cancer Patients in Mainland China: A Cross-Sectional Study - Xianghua Xu; Meijun Ou; Chanjuan Xie; Qinqin Cheng; Yongyi Chen (Pain Research and Management)
Background. Pain acceptance is associated with disability, pain interference, depression, and anxiety. Few studies have been conducted on the acceptance of cancer pain and its correlates. Objectives. The aim of this study was to examine the level and correlates of pain acceptance in cancer patients from mainland China. Setting and Participants. The study comprised 156 cancer patients in a tertiary cancer hospital in Hunan Province of China. Design. The study is based on a cross-sectional survey design. Subjects and Methods. The 8-item Chronic Pain Acceptance Questionnaire (CPAQ-8) was completed by 156 cancer patients with chronic pain from a tertiary cancer hospital. Demographics, pain, and negative mood assessed by the Hospital Anxiety and Depression Scale (HADS) were explored in relation to the CPAQ-8 scores using descriptive univariate analysis. Results. For the 156 patients, the mean CPAQ-8 score was 25.99 (SD = 8.56; range: 9 to 44). The scores were associated with age, gender, marital status, pain duration, number of pain sites, and duration of taking analgesics. The total scores on the CPAQ-8 and its two subscales (activity engagement and pain willingness) were negatively correlated with the HADS scores. Conclusions. The findings suggest that the prevalence of pain acceptance is relatively low for Chinese cancer patients. The cancer pain acceptance is affected by age, gender, pain duration, number of pain sites, and duration of taking analgesics. The acceptance of cancer pain is negatively correlated with depression and anxiety. Therefore, patients with risk factors for low pain acceptance should receive more attention in Chinese medical settings.